Structural analysis of eight novel and 112 previously reported missense mutations in the interactive FXI mutation database reveals new insight on FXI deficiency - Saunders, Rebecca E.; Shiltagh, Nuha; Gomez, Keith; Mellars, Gillian; Cooper, Carolyn; Perry, David J.; Tuddenham, Edward G.; Perkins, Stephen J. (Thrombosis and Haemostasis, 2009)
Factor XI (FXI) functions in blood coagulation. FXI is composed of four apple (Ap) domains and a serine protease (SP) domain. Deficiency of FXI leads to an injury-related bleeding disorder, which is remarkable for the lack of correlation between bleeding symptoms and FXI coagulant activity (FXI:C).The number of mutations previously reported in our interactive web database (http://www.FactorXI.org) is now significantly increased to 183 through our new patient studies and from literature surveys. Eight novel missense mutations give a total of 120 throughout the FXI gene (F11).The most abundant defects in FXI are revealed to be those from low-protein plasma levels (Type I: CRM-) that originate from protein misfolding, rather than from functional defects (Type II: CRM+). A total of 70 Ap missense mutations were analysed using a consensus Ap domain structure generated from the FXI dimer crystal structure. This showed that all parts of the Ap domain were affected.The 47 SP missense mutations were also distributed throughout the SP domain structure.The periphery of the Ap β-sheet structure is sensitive to structural perturbation caused by residue changes throughout the Ap domain, yet this β-sheet is crucial for FXI dimer formation. Residues located at the Ap4:Ap4 interface in the dimer are much less directly involved. We conclude that the abundance of Type I defects in FXI results from the sensitivity of the Ap domain folding to residue changes within this, and discuss how structural knowledge of the mutations improves our understanding of FXI deficiencies.
Keywords: Factor XI; coagulation; mutations; web database